The Role of The Role of Customer Relationship Management (CRM) in Enhancing Public Satisfaction with Smart City Services - Paramita Paramita (Acceleration, Quantum, Information Technology and Algorithm Journal, 2025)
This study aims to explore the role of Customer Relationship Management (CRM) in enhancing public satisfaction with smart city services. A literature review method was employed by analyzing 10 previous studies from 2015 to 2025 that are relevant to the implementation of CRM in smart city service applications. The findings reveal that CRM contributes to three key aspects: (1) CRM improves responsiveness to public complaints, (2) CRM encourages public engagement, and (3) CRM facilitates access to public service information. Despite its many benefits, the study also identifies several challenges in CRM implementation, such as technological readiness, limited human resources, and the level of digital literacy among citizens. Therefore, the successful implementation of CRM in smart city applications requires appropriate strategies, including public education and strengthening of technological infrastructure. This study is expected to provide insights for governments and stakeholders in optimizing CRM to improve the quality of public services in smart city applications.